Case Report: Management of Ineffective Breathing Patterns in Pulmonary Tuberculosis Patients Using Orthopnea Positioning - Hidayat, Mukhlish; Mohammad Shiddiq Suryadi; Irfan Asmawi (Universitas Nazhatut Thullab Al- Muafa Sampang, 2025)
Background: Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. The disease can cause damage or fibrosis of the respiratory tract and lung tissue, characterized by shortness of breath and cough. Ineffective breathing patterns are inspiratory and or expiratory processes that do not provide adequate ventilation characterized by the main problem of dyspnea which is the main complaint in Tuberculosis. Objective: to describe the effectiveness of the application of orthopnea position on the ineffective breathing pattern in tuberculosis patients. Methods: In compiling this case study the author used a descriptive method with a nursing process approach consisting of assessment, diagnosis, planning, implementation and evaluation. Results: After applying the orthopnes position to 2 patients, the evaluation results on day 3 on Mrs. “H” obtained data with the results after therapy: Dyspnea (Decreased), Use of breathing muscles (Decreased), Lengthening of the expression phase (Decreased), Nasal lobe breathing (Decreased), Breathing frequency (24x/m). While Mrs. “S” after therapy obtained data with the results after therapy Dyspnea (Decreased), Use of breath assist muscles (Decreased), Expression phase lengthening (Decreased), Breathing frequency (22x / m) Problem Resolved. Conclusion: Nursing care with the implementation of orthopnea positioning in 2 patients can be concluded to be effective in overcoming ineffective breathing patterns.